Análise de conflitos por uso de recursos hídricos na área de atuação do Comitê de Bacia Hidrográfica da Margem Esquerda do Rio Cuiabá - Moraes, Gabriel Figueiredo de (2019)
Demographic growth, disorderly occupation of the soil, and expansion of agriculture have led to problems of scarcity and degradation of water resources and, consequently, the impairment of multiple uses of water. In this context critical situations in water resources as a result of the crisis of governance, management failures and management of institutions, has influenced human and ecosystemic well-being. From the perspective of a water scarcity scenario, the overall objective of this study is to analyze the occurrence of conflicts due to the use of water resources in the area of interest of the Cuiabá River Left Bank Affluent Basin Committee, based on demand and availability water bodies. The methodological procedures were divided into three stages: i) diagnosis of the use of water resources, through a database of grants from the State Department of Environment (SEMA) and the National Water Agency (ANA) ii) quantification of availability surface water, by means of ANA historical series of flows and water availability of the SEMA and iii) water balance based on the uses and flow rate. A total of 366 concession processes were carried out, enabling the verification of the most representative use purposes in the Cuiabá River basins, which are energy generation, sanitary sewage and water supply, accounting for 43.15 %, 25.13 % and 14.38 %, respectively. Concerning water availability, the CBH Cuiabá ME area has a Q95 flow of more than 70 m3 / s in the Cuiabá river, greater than 10 m3/s in the Aricá-Açu River and, varying from 1 to 10 m3 / s, in the Aricá-Mirim, Coxipó and Coxipó-Açu rivers. The total flow offered in the stretches indicates a total water availability of 599.96 m3/s, of which 16.79 m3/s is used, representing only 2.79 %. Based on the classification of the remaining flow, it was observed the occurrence of quantitative conflicts in the Serragem and Jangada river basin. Regarding the application of the water withdrawal index, it was noted that the basin presents a very comfortable water demand and availability ratio, with 81 % of its rivers framed as in an excellent situation. In addition, 8 % of the basin rivers were classified as "disturbing", 3 % as "critical" and 8 % as "very critical". In the analysis of conflict for quality, it was observed its occurrence only in the hydrographic basin of the Coxipó river. It is concluded that the application of conflict analysis is an important tool for the management of water resources, providing subsidies for decision making, allowing the planning and identification of water bodies by the management body, allowing to identify areas where there are larger water and critical areas in relation to the use of water resources.